2012
DOI: 10.1111/j.1939-1676.2012.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heart Failure on Dipeptidyl Peptidase IV Activity in Plasma of Dogs

Abstract: We did not find evidence that plasma DPP4 activity is responsible for the "BNP resistance" in overt congestive HF, but it may be implicated in early stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…DPP-4 removes the 2 amino-terminal amino acids from B-type natriuretic peptide (BNP) to produce BNP , which induces less natriuresis, diuresis, and vasodilation than BNP (1-32) [6]. Increased DPP-4 activity is associated with the pathophysiology of heart failure [7]. DPP-4 inhibitors have been thought to have cardio-protective effects owing to increases in the incretin hormones levels and BNP bioavailability in type 2 diabetes mellitus (T2DM) patients.…”
Section: Introductionmentioning
confidence: 99%
“…DPP-4 removes the 2 amino-terminal amino acids from B-type natriuretic peptide (BNP) to produce BNP , which induces less natriuresis, diuresis, and vasodilation than BNP (1-32) [6]. Increased DPP-4 activity is associated with the pathophysiology of heart failure [7]. DPP-4 inhibitors have been thought to have cardio-protective effects owing to increases in the incretin hormones levels and BNP bioavailability in type 2 diabetes mellitus (T2DM) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Increased DPP4 activity is associated with pathophysiology of HF. DPP4 activity was measured in dogs with different degree of heart failure (HF): DPP4 activity increased linearly with body weight and was significantly higher in heart failure class 1 compared with healthy heart and heart failure class 3 demonstrating that DPP4 activity could be involved in early stages of heart failure [22]. …”
Section: In Vivo Evidencementioning
confidence: 99%
“…Dipeptidyl peptidase‐4 (DPP‐4) rapidly inactivates incretins with a half‐life of a few minutes; therefore, DPP‐4 inhibitors or gliptin are currently used in the treatment of type 2 diabetes mellitus (T2DM). Recently, both experimental and clinical studies have suggested that DPP‐4 inhibitors can modulate cardiovascular function by ameliorating ischaemia‐reperfusion injury, reducing the atherosclerotic lesions and vascular inflammatory reaction, and protecting the heart from acute myocardial ischaemia . There are a number of underlying molecular mechanisms involved in angiopathy associated with diabetes that are recognized, where there is impaired nitric oxide (NO) bioavailability, to be the main cause of endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%